İlkokul 2. ve 3. Sınıf Öğrencilerinin Oynadıkları Oyunların İncelenmesi - Öztabak, Muhammet Übeydullah (Muş Alparslan Üniversitesi, 2017)
The aim of this research is to examine the games played by the 2nd and 3rd grade primary school students. The research was conducted at a public school in Bakırköy district, Istanbul. In the research, "Case Study" was used as qualitative research method. The study group consisting of 80 students included 22 boys and 18 girls in 2nd grade, 22 boys and 18 girls in 3rd grade. The data of the study were obtained from the focus group interviews consisting of open-ended questions prepared by the researcher. According to the results of the research, male students were found to be more addicted to playstation, tablet and computer games than female students. Even though there is not much difference between the ages of 2nd and 3rd grade students, it is determined that there is a visible difference in the content of the games they play.

Bu araştırma, ilkokul 2. ve 3. sınıf öğrencilerinin günümüzde oynadıkları oyunların incelenmesini amaçlamaktadır. Araştırma, İstanbul ili Bakırköy ilçesinde bulunan bir devlet okulunda gerçekleştirilmiştir. Araştırmada, nitel araştırma yöntemlerinden “Durum Çalışması” deseni kullanılmıştır. Araştırmanın çalışma grubunu, 2. sınıf öğrencisi 22 erkek, 18 kız; 3. sınıf öğrencisi 22 erkek, 18 kız olmak üzere toplam 80 öğrenci oluşturmaktadır. Araştırmanın verileri, araştırmacı tarafından hazırlanan açık uçlu sorulardan oluşan odak grup görüşmeleriyle elde edilmiştir. Araştırmada sonuçlarına göre, erkek öğrencilerin play station, tablet ve bilgisayar oyunlarına kız öğrencilere oranla daha düşkün oldukları görülmüştür. 2. ve 3. sınıf öğrencilerinin arasında büyük bir yaş farkı olmamasına rağmen oynadıkları oyunların içeriğinde gözle görülür bir farkın olduğu saptanmıştır.
Examination of the Games Played by 2nd and 3rd Grade Primary School Students
anemon
Keywords: Games; Children's Games; Primary School Students; Virtual Games; Oyun; Çocuk Oyunları; İlkokul Öğrencileri; Sanal Oyunlar